The Valuation Implications of Employee Stock Option Accounting for Profitable Computer Software Firms - Bell, Timothy B.; Landsman, Wayne R.; Miller, Bruce L.; Yeh, Shu (The Accounting Review, 2002)
We use the Ohlson (1995, 1999) and Feltham and Ohlson (1999) valuation models to investigate the market's perception of the economic effect of employee stock options (ESOs) on firm value for a sample of 85 profitable computer software companies. Our results suggest that the market appears to value these firms' ESO expense not as an expense but as an intangible asset (even after controlling for the endogeneity bias arising from the mechanical relation between ESOs and the underlying stock prices). However, we also find a conflict between: (1) the positive manner in which investors appear to value ESO expense, and (2) the negative relation between current ESO expense and future abnormal earnings. This conflict not only could be an artifact of the restrictiveness of the abnormal earnings forecasting equation we estimate, but it also calls into question whether investors assess correctly the effect of ESOs on profitable software firm value.